Determination of phosphatidylinositol-3-kinase gene copy number and protein expression in nasopharyngeal carcinoma by real-time PCR and immunohistochemistry - Firoozinia, Mohammad (2013)
Phosphatidylinositol 3-kinase (PI3K) is a well-known lipid kinase which belongs to a family of enzymes involved in cellular functions such as proliferation, cell growth, motility, and differentiation. The PI3K/AKT pathway is an intracellular signaling pathway, which is important in cancer. The pathway, with PTEN gene (tumor suppressor) and PIK3CA oncogene, is implicated in the insensitivity of cancer tumors to IGF1 and insulin AKT is recruited to the cell membrane using the PH domain ahead PI3K activation, and phosphatidyl-3,4,5-triphosphate (PIP3) is created. The PI3K/AKT signaling pathway is involved in many cellular processes associated with tumorigenesis, together with cell proliferation adhesion and spread. Gene amplification in the PIK3CA gene has been reported in many human cancer types such as cancers of colon, breast, brain, liver, stomach and lung. The purpose of this research is to determine whether there is a significant association of increased PIK3CA amplification and PI3K p110α protein expression in nasopharyngeal carcinoma tissues. Real-time quantitative PCR and immunohistochemistry were used to determine the PIK3CA gene copy number and to detect protein expression, respectively. The results obtained were analyzed and the ratio of PIK3CA to β-actin gene copy number was calculated. Positive PIK3CA gene amplification was defined as a copy number of ≥4. Also, PI3K p110α protein expression was scored as 0, 1+, 2+ and 3+. The scores of 2+ and 3+ were considered as positive for PI3K p110α protein expression. Sixty-six nasopharyngeal tumor samples were studied for increased PIK3CA gene amplification, and PI3K p110α protein expression was also analyzed in 36 apparently normal adjacent tissues of these 66 tumor samples. Overall, 62 out of 66(93%) NPC samples showed a significant increase in PIK3CA gene copy numbers. 37 out of 22(62%) of tumor sample showed negative staining, and 29 out of 22(44%) showed positive staining for PI3K p110α expression. High frequency of PIK3CA gene copy number has been reported in 40% of nasopharyngeal carcinoma in China which is consistent with our results. Correlation of PIK3CA amplification showed no significant relationship with age in 4 groups (P= 0.443, P= 0.605, P= 0.266, P= 0.2695), gender (P= 0.290), and race (P= 0.500) in nasopharyngeal carcinoma. But we have identified a significant correlation between PIK3CA amplification and histological type (P= 0.001). Correlation of PI3K p110α protein expression showed no significant relationship with age in 4 groups (P= 0.206, P= 0.564, P= 0.552, P= 0.925), gender (P= 0.900), race (P= 0.556) and histological type (P= 0.864) in nasopharyngeal carcinoma. Correlation between PIK3CA gene copy number and PI3K p110α protein expression showed that there is no relationship (p=0.755) between them. There was no significant correlation between PIK3CA amplification/expression and age in ovarian clear carcinoma, and there was also no correlation between PIK3CA amplification and p110α protein expression in head and neck squamous cell carcinoma has been stated, which is consistent with our finding in nasopharyngeal carcinoma. Amplification of PIK3CA was frequent in nasopharyngeal carcinoma. Our finding shows that there is a relationship between PIK3CA gene amplification and histological types I (WHO classification, based on light microscopy) in nasopharyngeal carcinoma. In conclusion, our data suggest that PIK3CA has an important role in tumors; and gene amplification is a relatively common mechanism in activating PIK3/Akt signaling pathway in nasopharyngeal carcinoma. The limitation of this study is that the sample for the present study comprised of 74 cases. This sample is only a very small number of the entire population in the country. In particular, the histological type I of nasopharyngeal carcinoma is low in Malaysian patients. Also, during the real-time PCR experiment, the positive control DNA did not show similar Ct values in each experiment, which emerged as one of the limitations of our research. Therefore, research studies with much larger sample size would be required to ensure appropriate generalization of the findings of the study.